Dynamics Control with Modified Wavelet Function in Turbo Decoding Algorithm - LiYa Ding (2011 International Conference on Control, Automation and Systems Engineering, 2011)
A modified Mexican hat wavelet function is developed to control dynamical region in turbo decoding algorithm. On average, compared to the classical turbo decoding algorithm without control, the control method achieves 0.5 dB improvement in signal-to-noise.